x4+3x3-7x2-27x-18
= x4+3x3+2x2-9x2-27x-18
= x2(x2+3x+2)-9(x2+3x+2)
= (x2+3x+2)(x2-9)
Vốn là áp dụng cách khác nhưng mình ngại làm lắm
ta có:x4+3x3 -7x2 -27x-18
= x4+3x3 +2x2-9x2-27x-18
= x2(x2+3x+2)-9(x2+3x+2)
= (x2+3x+2)(x2 -9)
=(x2+x+2x+2)(x-3)(x+3)
=(x+1)(x+2)(x-3)(x+3)
\(x^4+3x^3-7x^2-27x-18\\ =x^4+2x^3+x^3-9x^2+2x^2-18x-9x-18\\ =\left(x^4+2x^3-9x^2-18x\right)+\left(x^3+2x^2-9x-18\right)\\ =x\left(x^3+2x^2-9x-18\right)+\left(x^3+2x^2-9x-18\right)\\ =\left(x+1\right)\left(x^3+2x^2-9x-18\right)\\ =\left(x+1\right)\left[\left(x^3+2x^2\right)-\left(9x+18\right)\right]\\ =\left(x+1\right)\left[x^2\left(x+2\right)-9\left(x+2\right)\right]\\ =\left(x+1\right)\left(x^2-9\right)\left(x+2\right)\\ =\left(x+1\right)\left(x+3\right)\left(x-3\right)\left(x+2\right)\)